1980
DOI: 10.1007/bf00504235
|View full text |Cite
|
Sign up to set email alerts
|

The lack of a pronounced preference of prenalterol for the beta-l-adrenoceptor subtype

Abstract: The beta-sympathomimetic effect of prenalterol was investigated on the electrically driven left atrium as well as on the tracheal chain of the guinea pig. 1. On the atrium driven at 2 Hz prenalterol caused a positive inotropic effect with a pD2-value of 7.0 +/- 0.08 (N = 4). Compared to isoprenaline (1.0) its intrinsic activity amounted to 0.3. 2. On the tracheal chain prenalterol caused very little relaxation. Its intrinsic activity was virtually negligible when compared with those of fenoterol (1.0) or norad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In fact, prenalterol inhibited the effect of terbutaline competitively. Rohm et al (1980) found that prenalterol inhibited the relaxing effect of noradrenaline on the guinea-pig trachea. This is com~atible with the view that prenalterol is a non-selective /?-adrenoceptor ligand with absolute PI-selective, partial, agonistic activity (Hedberg et al 1980).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, prenalterol inhibited the effect of terbutaline competitively. Rohm et al (1980) found that prenalterol inhibited the relaxing effect of noradrenaline on the guinea-pig trachea. This is com~atible with the view that prenalterol is a non-selective /?-adrenoceptor ligand with absolute PI-selective, partial, agonistic activity (Hedberg et al 1980).…”
Section: Discussionmentioning
confidence: 96%
“…Thus thechoice of steroid in experiments with tracheal smooth muscle may be critical for the estimation of potency and efficacy of bronchodilators. This is illustrated by the failure to detect the relaxing effect of prenalterol on the carbachol contracted ( I pmol litre-') trachea when corticosterone is substituted for 178-oestradiol (compare Rohm et al 1980with Kenakin & Beek 1980.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the efficacy of prenalterol in rat heart is intermediary to the efficacy in cat papillary muscle (Hedberg & Mattsson 1981) and guinea pig left atrium (Rohm et al 1980).…”
Section: Discussionmentioning
confidence: 94%
“…In effect, binding experiments have shown that prenalterol binds non-selectively to both 0, -and P2-adrenoreceptors (Johansson & Waldeck, 1980; Hedberg, Mattson & Carlsson, 1980) and while no differences in tissue affinity could be demonstrated, different stimulus-response relationships of different tissues were observed (Kenakin & Black, 1980) so that categorization of this drug is perhaps not so clear-cut (Rohim, Wagner & Schumann, 1980). The inotropic effect is reported to be evident without a significant increase in heart rate (Carlsson, Dahlof & Hedberg, 1977).…”
Section: Introductionmentioning
confidence: 95%
“…Prenalterol [S-( -)-I -4 hydroxyphenossy)-3-isopropylaminopropanol-2-hydrochloride] is a new drug from Hassle-Astra Pharmaceutical, AB, which activates P,-receptors in the heart in doses which have no significant effect on &receptors in the .lungs and blood vessels (Ariniego et at., 1979; Hutton et ul., 1980;Johnsson et al, 1978; Knaus et at., 1978, Ronn el at., 1980). In effect, binding experiments have shown that prenalterol binds non-selectively to both 0,and P2-adrenoreceptors (Johansson & Waldeck, 1980; Hedberg, Mattson & Carlsson, 1980) and while no differences in tissue affinity could be demonstrated, different stimulus-response relationships of different tissues were observed (Kenakin & Black, 1980) so that categorization of this drug is perhaps not so clear-cut (Rohim, Wagner & Schumann, 1980). The inotropic effect is reported to be evident without a significant increase in heart rate (Carlsson, Dahlof & Hedberg, 1977).…”
Section: Introductionmentioning
confidence: 99%